Pemanfaatan Media Wordwall Sebagai Upaya Meningkatkan Keaktifan Siswa Kelas X Pada Pelajaran Ekonomi - Dewi, Puspita (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study aims to describe the use of the interactive learning media Wordwall in increasing student activeness in Economics learning for Grade X at SMAN 1 Pringgarata. The main problem is the low level of student participation caused by conventional teaching methods and the limited use of engaging digital media. Using a descriptive qualitative method through observation, interviews, and documentation, the study involved the Economics teacher and Grade X-7 students. The results show that Wordwall has a positive impact, as seen from the increased enthusiasm, participation in discussions, and students’ interest in learning. The supporting factor is students’ interest in digital media, while the obstacles include limited devices and internet access. It is concluded that Wordwall is an effective alternative learning media to enhance student participation and create a more interactive, varied, and meaningful learning environment.